High-dose radiation induces dendritic cells maturation by promoting immunogenic cell death in nasopharyngeal carcinoma - Zeng, Xianlin; Jin, Xianhuai; Leng, Ji; Zhang, Shuai; Wang, Yun; Chen, Jin; Zhang, Shichao; Teng, Lijing; Hu, Zuquan; Zhou, Shi; Zeng, Zhu; Long, Jinhua (Frontiers in Immunology, 2025)
Aim and backgroundDue to the radiosensitivity and deep anatomical location of nasopharyngeal carcinoma (NPC), radiotherapy serves as the cornerstone of standardized treatment for this malignancy. Beyond its cytotoxic effects, radiotherapy can serve as an immunological adjuvant by inducing immunogenic cell death (ICD). Dendritic cells (DCs), as potent antigen-presenting cells, play a critical role in tumor immunotherapy, but their exact role in the ICD process of NPC remains unclear. The effects of high-dose radiation (≥2 Gy) on DCs and the type of immune response it elicits in NPC have not been fully elucidated.MethodsAn in vitro study was conducted to assess whether ICD of NPC 5-8F cells induced by high-dose radiation could regulate the immune response of DCs. Specifically, the maturation and antigen-presenting capacity of DCs were evaluated following co-culture with NPC cells exposed to high-dose radiation.ResultsHigh-dose radiation was found to induce ICD in NPC 5-8F cells, as evidenced by increased pro-inflammatory factor levels and reduced anti-inflammatory factor levels in the cell culture supernatant. Co-culture with NPC cells exposed to high-dose radiation for 15 minutes significantly enhanced the expression of surface molecules on DCs, promoting their immune sensitization.ConclusionHigh-dose radiation-induced apoptosis of NPC 5-8F cells is a form of ICD, which plays an important role in regulating DC immune function. These findings provide insight into the immunomodulatory effects of radiotherapy in NPC and its potential to enhance tumor immunotherapy through DC activation.